David Bowie is... Hyperreal - Whittall, Edward (InTensions, 2014)
David Bowie is…, the recently ended exhibit at the Art Gallery of Ontario, stands in stark contrast to a similar exhibit mounted by Marina Abramovic at the MOMA entitled The Artist is Present. Unlike Marina Abramovic’s insistent, troubling presence, David Bowie’s body is absent. The exhibit offers the performative figure of “Bowie” as simulacrum, a “real without origin or reality: a hyperreal” (Baudrillard 1994, 1). The simulacral “Bowie” is presented as a de-centered, dis-oriented subject, transecting gender and performance boundaries as he effortlessly moves through physical and artistic geographies. This paper argues that the exhibit merely performs the subversive, “demonic” (Deleuze 1990, 258) character of the simulacrum, and by doing so closes it off from its radical potential to challenge the neo-liberalized space of the museum.